"The Sentence in Grammatical Thought According to Mahdi al-Makhzoumi: A Study in Concepts and Categories" - YAZID mehamed, salem (El Omda in Linguistics and Discourse Analysis, 2018)
This study aims to examine the most important concepts and classifications that Mahdi al-Makhzoumi proposed regarding the sentence, considering it one of the most significant grammatical and linguistic issues, discussed both in classical and modern studies. It seeks to highlight his main contributions to the study of the sentence in comparison with earlier studies, as well as the significance of his work from the perspective of modern linguistic research. It is certain that in contemporary linguistic studies, syntax is primarily concerned with the study of the sentence.